First evidence of domoic acid production in Pseudo-nitzschia calliantha cultures from the central Adriatic Sea - Arapov, Jasna (Array, 2020)
In this study, three isolates of the potentially toxic diatom genus Pseudo-nitzschia were analysed for morphological and toxicological features. Cultures of Pseudo-nitzschia were established from seawater samples collected from the southern part of the Velebit Channel (central Adriatic Sea) during February 2019. All culture isolates were identified by scanning electron microscopy (SEM) as Pseudo-nitzschia calliantha. Domoic acid (DA) production was confirmed in all isolates analysed. The highest concentrations of cellular DA were found in early culture stages, with the lowest cell abundance, for all P. calliantha isolates. This study is the first to report DA production by P.calliantha isolated from the Adriatic Sea.